Application of Liquid Smoke from Coconut Shell in Tandipang (Dussumeiria Acutta) Smoked Fish To Extend Shelf Life - Dyah Ayu Rakhmayeni; Tatty Yuniarti; Sukarno Sukarno (Faculty of Fisheries and Marine Universitas Airlangga, 2020)
Highlightaw on smoked tandipang fish analyzed.Peroxide value on smoked tandipang fish analyzed.TPC on smoked tandipang fish analyzed.The shelf life of liquid smoked tandipangfish stored at 27o C was obtained the value of t = 23.2 in units of weeks or 5.8 months of storage.AbstractFumigation using liquid smoke produces smoked fish products with a smoky flavor character and can increase shelf life. The research objective was to determine the shelf life of the tandipang fish which was processed using liquid smoking. The test was carried out by storing smoked fish in an incubator at different temperatures 30 °C, 40 °C, and 50 °C with three replications for 5 weeks (35 days). The samples prepared at each temperature were kept in an incubator for five weeks. The parameters tested for estimating shelf life are using the test data aW (activity water), peroxide number, and TPC (total plate count). The three parameters are selected by one parameter to calculate the shelf life of liquid smoked tandipang fish which is considered to greatly affect the quality degradation during storage. The aw parameter is used to determine the shelf life because it has a high R2 value with an activation energy of 86972.75 J / mol.K. Estimation of shelf life of liquid cured fish at room temperature using aw parameter is 23.2 weeks or 5.8 months.